The risk management of safety and dependability : a guide for directors, managers and engineers - Wong, W. (CRC Press ; Woodhead Pub., 2010)
The issue of risk should be embedded into the mindset of every engineer and manager to improve safety and dependability. Companies can be held accountable through law when a gross failing in health and safety management has fatal consequences. Here risk management, the organisational structure required and the main factors needed for its successful execution are explored. What risks must be managed as a legal requirement? How is risk quantified? What methods can be used to reduce risk? Such questions are addressed, alongside case histories of disasters to illustrate failures in risk management. In an easy-to-read and accessible way, The risk management of safety and dependability presents the key factors involved in successful risk management, so that even non-experts in small and medium-sized organisations, as well as engineers and managers, can apply sound safety and dependability principles. Complies with the recommendations of the Engineering Technology BoardAssesses ways of recognising hazards and procedures for reducing risk in the design of processes, plant and machineryProvides detailed accounts of three major disasters and describes the lessons to be learnt in relation to risk management.